Penerapan Internet of Things (IoT) Pada Sistem Kendali Lampu Berbasis Mobile - Muzawi, Rometdo; Kurniawan, Wahyu Joni (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2018)
Internet of things (IoT) is a hardware (Raspberry Pi) that can connect to the internet with the aim to expand the internet network that is connected thoroughly to the hardware. The development of the Internet of things (IoT) has been widely used, especially in this day and age, one of the utilization of this IoT technology is the control of electronic room light equipment through global network controlled via smartphone that can be operated remotely. This research aims to build a remote-control device by utilizing internet technology to perform the process of controlling the lights based on the Internet of things (IoT). This research is done by building a prototype with mobile based application using python and php programming language. In this research there is a feature of controlling the room lights with the first condition of control of one lamp used to turn one room light and the second condition is used to turn the lights simultaneously.